2007
DOI: 10.1161/circulationaha.106.681247
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis Secondary Prevention Performance Measures After Coronary Bypass Graft Surgery Compared With Percutaneous Catheter Intervention and Nonintervention Patients in the Get With the Guidelines Database

Abstract: Background— The American Heart Association Get With the Guidelines-Coronary Artery Disease program facilitates patient and physician compliance with proven atherosclerosis risk reduction strategies with collaborative learning sessions, teaching materials, predischarge online check lists, and web-based performance measure feedback for continuous quality improvement. Patients having coronary artery bypass graft surgery (CABG) may be subject to different care processes, nursing unit pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 21 publications
1
43
0
3
Order By: Relevance
“…[13][14][15][16][17] A large international observational registry (Reduction of Atherothrombosis for Continued Health [REACH]) of 37 154 patients with established atherosclerotic disease has shown that only 46.7% of patients at baseline and 48.2% at 1 year were taking OMT. 29 Although antiplatelet agents and lipid-lowering agents were used in more than two thirds of the SYNTAX patients, use of angiotensin-converting enzyme inhibitor and β-blockers was consistently below 50%, which is similar to the report from CABG patients in the Project of Ex-vivo Vein Graft Engineering via Transfection IV (PREVENT IV) trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17] A large international observational registry (Reduction of Atherothrombosis for Continued Health [REACH]) of 37 154 patients with established atherosclerotic disease has shown that only 46.7% of patients at baseline and 48.2% at 1 year were taking OMT. 29 Although antiplatelet agents and lipid-lowering agents were used in more than two thirds of the SYNTAX patients, use of angiotensin-converting enzyme inhibitor and β-blockers was consistently below 50%, which is similar to the report from CABG patients in the Project of Ex-vivo Vein Graft Engineering via Transfection IV (PREVENT IV) trial.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] However, limited published literature suggests that the use of medication for secondary prevention remains suboptimal after coronary revascularization, particularly after CABG. [11][12][13][14][15][16] This underuse of OMT might reflect medication nonadherence or issues with the healthcare system or may be related to a paucity of data, leading to an underestimation of importance of OMT and the misconception that continuing OMT may be of less value once diseased coronary arteries have been mechanically revascularized. 17,18 Recent controversies on the use of β-blockers, generally and in noncardiac surgery, and statins may further reduce prescription or compliance, [19][20][21][22] with potential consequences on long-term clinical outcomes.…”
mentioning
confidence: 99%
“…There were significant ( p < .01) differences in practices and changes in practice between institutions that conducted an institutional discussion of the Guidelines and those that did not. In general, the percentage of respondents reporting a change in practice within institutions that conducted an institutional discussion of the Guidelines was higher for many of the recommendations (Supplemental Digital Content, Appendix 2, Tables [15][16][20][21]. The percentage of respondents reporting highly or somewhat effective reductions in transfusion was significantly higher among institutions that conducted an institutional discussion of the Guidelines than those that did not (Supplemental Digital Content, Appendix 2, Table 13A).…”
Section: Resultsmentioning
confidence: 99%
“…Процент пациентов, выписанных c оптимальной медика-ментозной терапией может варьироваться в зависимости от диагноза, у пациентов разных возрастных групп (пожилые и молодые), гендерных особенностей (мужчины и женщины), различных оперативных вмешательств, а также различных учреждений [556]; пациенты, выписанные после недостаточ-ного лечения показывают более худший годовой прогноз [555] . В национальной программе ААС -«В соответствии с руководством» -назначение препаратов при выписке имеет определенную прогностическую значимость, являясь состав-ной частью комплексной оценки, которая включает оценку использования иАПФ, аспирина, бета-блокаторов, назначе-ние гиполипидемической терапии, а также отказ от курения, следование советам и консультациям .…”
Section: невыясненные моменты в доказательствахunclassified
“…Высокий уровень без-оговорочного соблюдения рекомендаций (100%) был выявлен в группе пациентов, перенесших ЧКВ (71,5%), затем в АКШ группе (65,1%), чем среди пациентов, не подвергшимся ника-ким вмешательствам . Многофакторный анализ 14 клиниче-ских показателей подтвердил, что статистически значимое соблюдение всех рекомендаций было в группе ЧКВ, чем в группе АКШ, самый низкий уровень зафиксирован среди пациентов, неперенесших никакие вмешательства [556] . Новое руководство ЕОК предоставляет собой список контр-ольных мер, необходимых при выписке из больницы для обеспечения снижения факторов риска и улучшения образа жизни пациентов с диагностированным ОКС для дальней-шего включения в программы профилактики ССЗ и дальней-шей реабилитации [557] .…”
Section: невыясненные моменты в доказательствахunclassified